I Don't Want to Wash My Hands! - Tony Ross (London, United Kingdom Andersen Press Ltd, 2017)
The Little Princess loves getting her hands dirty. The trouble is, she hates washing them. Until she learns all about the nasties, the dirties and all the other horrible things that lurk and make you ill . . .
Keywords: Healthy Lifestyle; Body Systems; PY-UOI - Who we are -- PY-UOI - Who we are